Macro-Micro Response Characteristics of Surrounding Rock and Overlying Strata towards the Transition from Open-Pit to Underground Mining - Xiaoshuang Li; Shun Yang; Yunmin Wang; Wen Nie; Zhifang Liu (Geofluids)
The macro-micro mining response of the surrounding rock and overlying strata towards the transformation from open-pit to underground mining is examined in the present study, based on the engineering background of the Jinning phosphate mine (Yunnan Phosphate Chemical Group Co., Ltd.) via simulations involving similar materials, digital photographic measurement technology, and numerical simulation. The mining deformation of the surrounding rock underground, and of the overlying strata, is shown to develop in three stages, namely: (1) small and local deformation, (2) continuous linear increase, and (3) the violent nonlinear collapse of the entire system. The internal distribution of stress in the surrounding rock and adjacent overlying strata of the inclined mined-out area is complicated. The degrees of pressure increase and pressure relief have an important relationship with the size of the mining space. The pressure relief is more complete close to the mined area, and the stress reduction decreases with increasing distance. The cracks propagate in arc shapes and have a tendency to penetrate into the upper and lower ends of the stope. The size of the excavation space plays a key role in the generation, propagation, and penetration of the cracks. Due to the disturbance of the first mining level and the increase in excavation depth, the rate of damage to the surrounding and overlying rock increases in the second mining level. This process generates more cracks, which accelerate the instability of the surrounding rock and overlying strata.